2022
DOI: 10.1002/anie.202204889
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Catalyzed Meinwald Rearrangement with an Unusual Regioselective and Stereospecific 1,2‐Methyl Shift

Abstract: The Meinwald rearrangement is a synthetically useful reaction but often lacks regioselectivity and stereocontrol. A significant challenge in the Meinwald rearrangement of internal epoxides is the non-regioselective migration of different substituents to give a mixture of products. Herein, an enzyme-catalyzed regioselective and stereospecific 1,2-methyl shift in the Meinwald rearrangement of internal epoxides is reported. Styrene oxide isomerase (SOI) catalyzed the unique isomerization of internal epoxides thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Concurrently, work from the Li lab also demonstrated that SOI is stereospecific for the trans migration by observing the transfer of a trans-methyl group over the cishydrogen. 25 Consistent with this observation, reactions with the (±)-trans-2a-3-d 1 showed no deuterium at C β and 25% deuterium at C γ . The theoretical maximum labeling at C γ would be 50%, indicating efficient transfer by SOI followed by hydrogen exchange due to enolization in protic solvent.…”
Section: Co-expression Of Soi and Obihsupporting
confidence: 59%
See 3 more Smart Citations
“…Concurrently, work from the Li lab also demonstrated that SOI is stereospecific for the trans migration by observing the transfer of a trans-methyl group over the cishydrogen. 25 Consistent with this observation, reactions with the (±)-trans-2a-3-d 1 showed no deuterium at C β and 25% deuterium at C γ . The theoretical maximum labeling at C γ would be 50%, indicating efficient transfer by SOI followed by hydrogen exchange due to enolization in protic solvent.…”
Section: Co-expression Of Soi and Obihsupporting
confidence: 59%
“…In the case with the deuterium cis to the phenyl ring ( (±)- cis -2a-3- d 1 ), the amino acid product contained deuterium only at C β , indicative of migration of the trans hydrogen (Figure b). Concurrently, work from the Li lab also demonstrated that SOI is stereospecific for the trans migration by observing the transfer of a trans -methyl group over the cis -hydrogen . Consistent with this observation, reactions with the (±)- trans -2a-3- d 1 showed no deuterium at C β and 25% deuterium at C γ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymatic cascades involving multiple enzymes in one pot allow for direct syntheses of valuable enantiopure chemicals from cheap starting materials. In addition to the use of nonchiral substrates, the use of easily available racemic substrates for enantioconvergent cascade conversion to enantiopure chemicals , has been receiving increasing attention. We are interested in developing a new enantioconvergent cascade to convert racemic epoxides into the corresponding enantiopure hydroxy acids.…”
Section: Introductionmentioning
confidence: 99%